BATASAN KEBEBASAN BERKONTRAK DALAM KONTRAK KONVENSIONAL DAN KONTRAK SYARIAH (IAIN Tulungagung, 2017)
This article aims to examine the limitations of the freedom of contract in conventional contract and Islamic contracts. In an agreement which establishes the basic principles of an agreement, the pacta sunt servanda principle, which has the sense that the agreement should be implemented by the parties to an agreement. And in an agreement there is a basis which is often used in a treaty as the basis of freedom of contract which provides for the freedom to determine whether someone will do or not do anything, with anyone one would conclude an agreement, as well as the content and form of an agreement. Freedom in the agreement does not mean freedom from regulation that applies. Independent free here means that it still remains under the control of law and norms applicable in a conventional agreement or treaty law. So that the agreement made by the parties do not violate the terms and conditions of existing agreements.Keywords: Kebebasan Berkontrak, Kontrak Konvensional, Kontrak Syariah